2005
DOI: 10.1097/01.ccm.0000182801.48137.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norepinephrine on static and dynamic preload indicators in experimental hemorrhagic shock*

Abstract: Our study confirms the superiority of dynamic variables (pulse pressure variation and systolic pressure variation) over static ones (right atrial pressure and pulmonary artery occlusion pressure) in assessing cardiac preload changes in hemorrhagic shock. However, norepinephrine could significantly reduce the value of these dynamic variables and mask a true intravascular volume deficit possibly by shifting blood from unstressed to stressed volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 26 publications
6
56
0
3
Order By: Relevance
“…37 However, an experimental study performed on dogs demonstrated that PPV decreased during an NE perfusion, despite increased vascular tone. 25 As mentioned earlier, the present result is related to the fact that vasopressors also diminish PPV by increasing venous return. Without doubt, our study confirms the hypothesis that vasopressors, such as NE and EPI, increase venous return and ventricular preload (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…37 However, an experimental study performed on dogs demonstrated that PPV decreased during an NE perfusion, despite increased vascular tone. 25 As mentioned earlier, the present result is related to the fact that vasopressors also diminish PPV by increasing venous return. Without doubt, our study confirms the hypothesis that vasopressors, such as NE and EPI, increase venous return and ventricular preload (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…By harvesting blood from the splanchnic territory, for example, catecholamines could increase the venous return and stroke volume, thereby diminishing preload dependency and dynamic indices. 25,26 In this regard, both PPV and SVV, which are valid indices of fluid depletion and fluid responsiveness, 24 diminished significantly under NE and EPI perfusions. The present hemodynamic changes were related to changes in venous return, as we demonstrated that IVCF, which diminishes during hypovolemia, increased following catecholamine infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by previous studies showing that pulse pressure variation (PPV), a good marker of preload dependency, decreased with noradrenaline administration (62,63). Recently, some studies have reported the effect of noradrenaline on Pmsf in humans, using the method of inspiratory hold manoeuvres described by Maas et al (104) in mechanical ventilated patients.…”
Section: Vasopressorssupporting
confidence: 74%
“…In these studies, the venoconstriction generated by noradrenaline recruits part of the unstressed volume into the stressed volume, due to small changes in venous compliance (57)(58)(59). This mechanism allows a transfer of blood volume from the splanchnic beds to the heart increasing right ventricular filling (60)(61)(62). (65) studied the effects of noradrenaline infusions on cardiac output in sixteen postoperative cardiac surgical patients using an increase of 20 mmHg in MAP as a target.…”
Section: For Blood Pressurementioning
confidence: 99%
“…NE is a potent vasoactive agent with alphaand beta-adrenergic properties that is widely used for the treatment of hypotension secondary to vasodilatation in hemorrhagic or septic shock (16), and that has no effect on cerebrovascular hemodynamics during intact circulation (17). The rationale for NE therapy during hemorrhagic shock is rooted in the fact that NE has been claimed to shift venous blood from unstressed to stressed vascular bed (18). Therefore, NE administration may support activation of the endogenous sympatho-adrenergic system in shifting blood volume to the central compartment, and thereby, preserving blood flow to the heart and brain.…”
mentioning
confidence: 99%